2018
DOI: 10.1111/jre.12524
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular matrix metalloproteinase inducer glycosylation in regulating matrix metalloproteinases in periodontitis

Abstract: We conclude that EMMPRIN glycosylation participates in the regulation of MMP-2 and MMP-9 production through mediating the interaction of HIOECs and HGFs. Inhibiting EMMPRIN glycosylation can reduce the activation of MMP-2 and MMP-9 and suppress the degradation of extracellular matrix (ECM) in the HIOEC/HGF co-culture model. Therefore, this study suggests that EMMPRIN glycosylation may affect the host immune-inflammatory response by regulating MMPs in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…LPS stimulation ( P < .01, Figure B). Protein levels of EMMPRIN/MMP‐2, 9 increased significantly, particularly for EMMPRIN and MMP‐9 ( P < .01, Figure E), and consistent with those of a previous study . In addition, qRT‐PCR results showed similar change trend for β‐catenin, EMMPRIN and MMP‐2, 9 mRNA levels as those of WB ( P < .05, Figure C; P < .001, Figure F).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…LPS stimulation ( P < .01, Figure B). Protein levels of EMMPRIN/MMP‐2, 9 increased significantly, particularly for EMMPRIN and MMP‐9 ( P < .01, Figure E), and consistent with those of a previous study . In addition, qRT‐PCR results showed similar change trend for β‐catenin, EMMPRIN and MMP‐2, 9 mRNA levels as those of WB ( P < .05, Figure C; P < .001, Figure F).…”
Section: Resultssupporting
confidence: 89%
“…LPS did not influence the expression of EMMPRIN, instead, 10 μg/mL Pg . LPS stimuli obviously upregulated EMMPRIN, which was one of the main targets of this study. Hence, we used 10 μg/mL Pg .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Overexpression of MMPs is necessary at the early step of tissue destruction to allow the periodontopathic bacterias, immune cells, and inflammatory factors to invade the healthy periodontium (Hannas et al, 2007;Kim et al, 2013;Ma et al, 2003). Our previous results (Yang et al, 2013;Xiang, Li, Dong, Cao, & Liu, 2009;Zhang et al, 2018) also demonstrated MMP-2, MMP-8, and MMP-9 are the prominent metalloproteinase in periodontitis and are responsible for the degradation of collagen I, II, and III in periodontal ECM, and basement membrane collagen IV.…”
Section: Introductionmentioning
confidence: 86%
“…MMPs are a family of Zn 2+ -containing neutral proteolytic enzymes that degrade extracellular matrix (ECM). Human MMPs are classified as collagenases, gelatinases, matrix lysins, membrane-type MMPs and other MMPs (14,15). The direct effects of MMPs in periodontal tissue destruction and degradation are involved in the development of periodontitis.…”
Section: Il-18 Promotes the Secretion Of Matrix Metalloproteinases Inmentioning
confidence: 99%